The identification of rurality at Nuts-3 level in Turkey - Özlü, Seda; Dedeoğlu Özkan, Sinem; Beyazlı, Dilek (TeMA - Journal of Land Use, Mobility and Environment, 2024)
Rural-urban interactions have become an even more important issue with global changes and developments. These areas, where population density and agricultural production are low, have a complex social, economic and natural structure that cannot be handled from a single perspective. This situation necessitates a multidimensional approach to rural areas and rurality. The study aims to address the socio-demographic and economic structure of Turkey’s provinces with a multidimensional approach and to analyze them comparatively. The data set of the study consists of 14 socio-demographic and 15 economic variables used in defining rural-urban areas. Three different clustering analysis methods (K-means, Ward, Two Step) were used in the study in which SPSS program was applied. As a result of the analyzes made with three clustering methods, the spatial distribution of the ruralness levels of the provinces was mapped and the variables that lead to cluster formation were determined. The results of these cluster analyses conducted with different methods at the NUTS-3 level in Turkey include a methodological discussion and a comparative determination. Although there are spatial differences as a result of the analysis of rurality with both socio-demographic and economic variables, the general similarity of the clusters formed by the three methods is significant. As a result, these processes, which are carried out comparatively with alternative clustering methods, are important in determining rural and urban areas and guide the production of healthy decisions and policies for the problems and potentials of settlements.